Increased Nitric Oxide Bioavailability and Decreased Sympathetic Modulation Are Involved in Vascular Adjustments Induced by Low-Intensity Resistance Training - Macedo, Fabrício N.; Mesquita, Thassio R. R.; Melo, Vitor U.; Mota, Marcelo M.; Silva, Tharciano L. T. B.; Santana, Michael N.; Oliveira, Larissa R.; Santos, Robervan V.; Miguel dos Santos, Rodrigo; Lauton-Santos, Sandra; Santos, Marcio R. V.; Barreto, Andre S.; et al. (Frontiers in Physiology, 2016)
Resistance training is one of the most common kind of exercise used nowadays. Long-term high-intensity resistance training are associated with deleterious effects on vascular adjustments. On the other hand, is unclear whether low-intensity resistance training (LI-RT) is able to induce systemic changes in vascular tone. Thus, we aimed to evaluate the effects of chronic LI-RT on endothelial nitric oxide (NO) bioavailability of mesenteric artery and cardiovascular autonomic modulation in healthy rats. Wistar animals were divided into two groups: exercised (Ex) and sedentary (SED) rats submitted to the resistance (40% of 1RM) or fictitious training for 8 weeks, respectively. After LI-RT, hemodynamic measurements and cardiovascular autonomic modulation by spectral analysis were evaluated. Vascular reactivity, NO production and protein expression of endothelial and neuronal nitric oxide synthase isoforms (eNOS and nNOS, respectively) were evaluated in mesenteric artery. In addition, cardiac superoxide anion production and ventricle morphological changes were also assessed. In vivo measurements revealed a reduction in mean arterial pressure and heart rate after 8 weeks of LI-RT. In vitro studies showed an increased acetylcholine (ACh)-induced vasorelaxation and greater NOS dependence in Ex than SED rats. Hence, decreased phenylephrine-induced vasoconstriction was found in Ex rats. Accordingly, LI-RT increased the NO bioavailability under basal and ACh stimulation conditions, associated with upregulation of eNOS and nNOS protein expression in mesenteric artery. Regarding autonomic control, LI-RT increased spontaneous baroreflex sensitivity, which was associated to reduction in both, cardiac and vascular sympathetic modulation. No changes in cardiac superoxide anion or left ventricle morphometric parameters after LI-RT were observed. In summary, these results suggest that RT promotes beneficial vascular adjustments favoring augmented endothelial NO bioavailability and reduction of sympathetic vascular modulation, without evidence of cardiac overload.